Accuracy and Completeness of ICD-10 Diagnostic Coding for Non-Communicable Diseases at Wismarini Hospital, Pringsewu: Gambaran Keakuratan Dan kelengkapan kode diagnosis ptm dengan menggunakan icd 10 di rumah sakit wismarini pringsewu - Putri Wulandari; Etanaulia Marsim (Jurnal Rekam Medis dan Informasi Kesehatan, 2025)
Medical records play an important role in health services, particularly through coding diagnoses according to ICD-10. The accuracy and completeness of diagnosis codes affect data quality, insurance claims, and health service delivery.Objective: To describe the accuracy and completeness of non-communicable disease (NCD) diagnosis codes using ICD-10 at Wisma Rini Hospital Pringsewu.Method: A descriptive quantitative study with a sample of 71 NCD medical records (30% of 237 population) in the first quarter of 2025, selected by random sampling. A checklist was used as the research instrument, analyzed with univariate methods. Of 71 records, 60 (84.51%) were accurate and 11 (15.49%) were inaccurate. Completeness analysis showed 56 (78.87%) were complete and 15 (21.13%) incomplete. Most NCD diagnosis codes at Wisma Rini Hospital Pringsewu were accurate (84.51%) and complete (78.87%). However, some inaccuracies (15.49%) and incompleteness (21.13%) remain, requiring improvements through stricter compliance with medical resume filling and coder training.